Effect of Briming treatment and boron element on germination properties of some Solanaceae species - Al-Arab, Mouhamed Ali Mahmoud AlHamoud; Al-Mohamed, Hussein Qadban (Journal of agricultural, environmental and veterinary sciences, 2023)
This research aims to study the effect of the Briming method (soaking the seeds in water with continuous air pumping) with the addition of different concentrations of boron (0 mg, 1 mg, 2 mg, 5 mg, and 10 mg) B/L on the germination properties of some seeds. Species to the Solanaceae family (tomatoes, peppers, eggplants).It has been shown through this research that this method increases the percentage and speed of germination and its homogeneity and is reflected positively on the growth of both seedlings and rootstock, and the best results were recorded in the treatment of 5 mg B / liter for pepper and eggplant.And that an increase in the concentration of boron above 10 mg B / liter led to adverse results, as the percentage of germination decreased, the seedlings dwarfed, and the size of the root system and its branches decreased for each of the eggplant and pepper.The best used concentrations of boron for eggplant and pepper are 5 mg B / liter, as it recorded a very significant increase that exceeded 45 and 35% for eggplant and pepper, respectively, compared with the control (direct cultivation without using the Priming method or any addition of boron) followed by the treatment with 2 mg B / liter, while Increase focus to10 mg B / liter negatively affects germination and growth. As for tomatoes, the best concentration corresponds to 10 mg B / liter, as the best percentage of germination was recorded in this treatment by about 18% compared to the direct cultivation control, followed by the treatment of 5 mg B / liter compared to the control.
Keywords: cultivation; Briming treatment; Boron; Solanaceae